Left Berneri, right Wolfe with a paper in her hand. Sale of 'War Commentary' and collection for 'Freedom Press Defence Fund'
Left Berneri, right Wolfe with a paper in her hand. Sale of 'War Commentary' and collection for 'Freedom Press Defence Fund'.